Scaredy Squirrel makes a friend - Watt, Melanie, 1975- (Toronto, ON : Kids Can Press, 2007)
Scaredy Squirrel, a squirrel who never leaves his nut tree because he's afraid of the unknown, finds someone perfectly safe to make friends with. Join him on his journey to friendship.
A Junior Library Guild selection.
Keywords: Squirrels -- Juvenile fiction; Squirrels -- Fiction